The Business of Consulting : the Basics and Beyond. - Biech, Elaine (John Wiley & Sons, Incorporated, 2019)
Everything you ever wanted to know about consulting--a practical roadmap for aspiring entrepreneurs Seismic changes occurring in the workforce are leading to more and more people entering the world of contract, freelance, and contingency work. Rapid changes in demographics and advances in technology have led companies and talent to engage in profoundly new ways and consulting is one of the keys to success. The New Business of Consulting is authentic and practical, and shares the knowledge and skills required to start and grow a successful consulting business. From how to make a smooth career transition, to how to determine a consulting fee, to how consultants inadvertently create a bad reputation, it covers everything you need to know to thrive and flourish in this competitive field. Covers contemporary topics, such as how to achieve success in the gig economy Discloses a reliable technique to land the clients you want Presents options to help you balance your life and your business Prepares you for naming your business, managing critical financial issues, and building a client relationship Shows you how to take your income and impact beyond working as a solopreneur The crucial start-up days of a consulting business may be frenetic and fraught with questions. This new edition provides sanity and answers all the questions. It includes practical tools, templates, and checklists that you can download and implement immediately.